From Two-Phase to Three-Phase: The New Electrochemical Interface by Oxide Electrocatalysts - Xu, Zhichuan J. (Nano-Micro Letters, 2017)
Electrochemical reactions typically occur at the interface between a solid electrode and a liquid electrolyte. The charge exchange behaviour between these two phases determines the kinetics of electrochemical reactions. In the past few years, significant advances have been made in the development of metal oxide electrocatalysts for fuel cell and electrolyser reactions. However, considerable gaps remain in the fundamental understanding of the charge transfer pathways and the interaction between the metal oxides and the conducting substrate on which they are located. In particular, the electrochemical interfaces of metal oxides are significantly different from the traditional (metal) ones, where only a conductive solid electrode and a liquid electrolyte are considered. Oxides are insulating and have to be combined with carbon as a conductive mediator. This electrode configuration results in a three-phase electrochemical interface, consisting of the insulating oxide, the conductive carbon, and the liquid electrolyte. To date, the mechanistic insights into this kind of non-traditional electrochemical interface remain unclear. Consequently conventional electrochemistry concepts, established on classical electrode materials and their two-phase interfaces, are facing challenges when employed for explaining these new electrode materials.